Analysis of the Ellis Model on Information Seeking Behavior of Library Science Department Students of Nusantara Islamic University on the Determination of Internship Places - Rusli, Fitri Anggraeni; Indah, Rosiana Nurwa; Syam, Rifqi Zaeni Achmad (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
Information is considered a basic need that supports decision-making. One of the information needs for students themselves is information related to internships. This study aims to analyze the information-seeking behavior of the Department of Library Science students, at Nusantara Islamic University in determining the place of internship using the Ellis Model. The method used is to use a descriptive qualitative approach through interviews and literature studies. The results showed that each student can be said indirectly through the stages of the model. So that factors and influences are known in the decision-making process to determine the internship place that will be chosen by students.